Uji Mortalitas Ulat Grayak (Spodoptera litura F.) Terhadap Ekstrak Tanaman Lidah Mertua (Sansevieria trifasciata Prain) - Gusthi Permatasari; Nova Hariani; Sus Trimurti (Universitas Lampung, 2020)
The tongue-in-law plant (Sansevieria trifasciata Prain) contains saponins, flavonoids, steroids and triterpenoids which are natural metabolites that have the potential to control agricultural pests such as armyworms (Spodoptera sp.). Therefore, the aim of this study was to determine the mortality and LC50 value for 72 hours of giving in-law tongue plant extract to Spodoptera litura and the length of the life cycle of S. litura in the laboratory. The research method used a completely randomized design (CRD). The extract of the tongue-in-law plant is obtained from the maceration process of the tongue-in-law plant with ethanol and then concentrated using a rotary evaporator until the thick extract is obtained. The results of the research on the ethanol extract of the tongue-in-law plant on the mortality of S. litura, found that the highest mortality was 63.6% at a concentration of 800 ppm and the lowest mortality value was 36.4% at a concentration of 200 ppm for 72 hours.Tanaman lidah mertua (Sansevieria trifasciata Prain) mengandung saponin, flavonoid, steroid, dan triterpenoid yang merupakan metabolit alami yang berpotensi untuk mengendalikan hama pertanian seperti ulat grayak (Spodoptera sp.). Oleh karena itu, tujuan dari penelitian ini adalah untuk mengetahui mortalitas dan nilai LC50 selama 72 jam pemberian ekstrak tumbuhan lidah mertua terhadap Spodoptera litura dan lamanya siklus hidup S. litura di laboratorium. Metode penelitian menggunakan Rancangan Acak Lengkap (RAL). Ekstrak tumbuhan lidah mertua diperoleh dari proses maserasi tumbuhan lidah mertua dengan etanol kemudian dipekatkan menggunakan rotary evaporator hingga diperoleh ekstrak kental. Hasil penelitian ekstrak etanol tumbuhan lidah mertua terhadap mortalitas S. litura didapatkan mortalitas tertinggi sebesar 63,6% pada konsentrasi 800 ppm dan nilai mortalitas terendah pada konsentrasi 36,4%. 200 ppm selama 72 jam.Kata kunci: mortalitas, Sansevieria trifasciata, Spodoptera litura DOI: http://dx.doi.org/10.23960/jbt.v8i3.21591